Local Community Empowerment Strategies In Developing Green Entrepreneurship In Climate Villages - Poppy Alvianolita Sanistasya; Lailatul Hijrah; Kayla Farya Arniandis; Filemon Youventis Masi (JURNAL ECONOMINA, 2026)
This study aims to formulate a local community empowerment strategy to drive a community based green entrepreneurship transition within the Climate Village (Kampung Iklim) program in the buffer zone of the New Capital City of Indonesia (Ibu Kota Nusantara - IKN), East Kalimantan Province. A qualitative approach was employed, utilizing interactive data condensation and a Litmus Test via Urgency, Seriousness, and Growth (USG) analysis, involving four climate villages and eight informants comprising village government officials and climate village administrators. The findings reveal that grassroots governance dynamics vary significantly. Furthermore, the analysis identifies management digitalization and transparency as the highest priorities for maintaining collective community trust. This study offers practical contributions to grassroots circular business models aimed at supporting sustainable regional climate resilience